A maze of responsibility - Flaker, Vito (Metodološki zvezki, 2023)
This paper is an attempt to deconstruct, formally decode the notion of responsibility fre-quently appearing in the process of deinstitutionalisation and long-term care provision.It is a Kafkian predicative category of subordination. Its value is determined by its twoobjects. “For what” we are responsible constitutes the substance of responsibility, “to what”constitutes its form and sense. By examining the substance of responsibility—for acts, thingsand people, we have derived the basic parameters, conditions constitutive of responsibility:loss (negative consequences), alienation, reification, removal of will and ascribing. Investi-gating the form of responsibility, of that to which we are responsible, we have schematicallydivided instances of responsibility into hierarchic and horizontal, as well as into reflexiveand transient. Intricacies of responsibility to authorities, public, community as well as tonear ones and the self are explored in their action and contemplative properties. Deinstitu-tionalisation on the one hand restores civic responsibility to the service users, on the otherit transmutes its very conditions. The imperative is to restore their will capacity, not toascribe acts to stigma, allow reappropriation and humanisation and to put the emphasison achievement and success. In the case of the key worker, we demonstrate a new patternof professional responsibility, in which acts are actors’ responsibility, while helpers areresponsible for service delivery, their own acts and for teamwork that will uphold theuser’s emancipation. In the transition to community, subordinative responsibility is beingtransformed into everyday responsiveness and common responsibility for humanity.
Keywords: deinstitutionalisation; dezinstitucionalizacija; guardianship; keyworker; odgovornost; odzivnost; responsibility; responsiveness; skrbništvo; social work; socialno delo